Testing of the mutagenic potential of N-(γ-aminobuturyl)-1-aza-15-crown-5 hydrochloride in Ames test microplate modification - M. Ya. Golovenko; V. B. Larionov; S. S. Basok; A. S. Reder (The State Expert Center of the Ministry of Health of Ukraine, 2019)
In recent years, studies in the field of chemical mutagenesis have undergone significant development, due to the introduction of a large number of different chemicals and scientific advances in the creation and use of new test systems, allowing a complete assessment of both mutagens themselves and their metabolites. The aim of the work was to determine possible induction of gene mutations under influence of hydrochloride N-(γ-aminobuturil)-1-aza-4,7,10,13-tetraozacyclopentadecan (TOCPD), which has nootropic, anxiolytic and anticonvulsant activity. The ability of TOCPD to induce gene mutations was evaluated in Ames test on strains Salmonella typhimurium ТА 98 (frame shift mutations) and ТА 100 (substitution point mutations). The compound was used at concentrations of 10, 100, 250, 500 and 1000 μg/ml. Standard mutagens were 2-nitrofluoren for Salmonella typhimurium ТА 98 and sodium azide for Salmonella typhimurium ТА 100 in test without metabolic activation. In an activation variant a microsomal activating mixture was used (S9 mix). In tests with activation for both strains, 2-aminoantracene was used. The µAmes kit, Moltox (USA) and Muta-ChromoPlate kit (Canada) were used in the work. The results were evaluated by the number of wells with mutated cells with medium color changing from purple to yellow. The obtained data showed that in the control and according to the action of corresponding mutagens, the percentage of wells with mutated cells corresponded to the standard parameters determined by protocol of the microplate test. For the action of TOCPD compound, no gene mutations were detected in both S. typhimurium ТА 98 and ТА 100 strains within the concentrations used.